Study of Antimicrobial Effects of Organic and Aqueous Extracts of Grains of Triticum sativum Lam. on Gram - positive and Gram-negative Bacteria - H Komeilizadeh; M Hakemi vala; M Kamalinejad; S Neshat ashofteh (Institue of Medicinal Plants, ACECR, 2008)
Background: Bacterial diseases are common in human life and antibiotics are commonly used to treat bacterial diseases. However, antibiotic therapy has the disadvantage of being faced with bacterial resistance. Fortunately experience shows that products prepared from medicinal plants can be used safely and successfully to treat bacterial diseases without presenting the disadvantages of side effects and bacterial resistance. Triticum sativum of Poaceae family has been used in Iranian traditional cure for many years ago. Then, the aim of this study was to determine antibacterial activity of wheat against some bacteria. Objective: Then, The aim of this study was to determine antibacterial activity of wheat against some bacteria. Methods: The extracts were prepared by the method of maceration using water, methanol, chloroform and petroleum ether as extraction solvents. The effect of the zone of inhibition of different concentrations (25, 50, 75, 100 mg/ml) of the prepared extracts on the above - mentioned bacteria was determined using Kirby- Bauer method and using the disk diffusion technique against Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, Pseudomonas aeruginosa. Results: The water extract of all concentrations (25, 50, 75, 100 mg/ml) showed no antibacterial effects. The methanol extract had a significant effect on Streptococcus pyogenes but a weak effect on Staphylococcus aureus. The chloroform extract had a weak effect on both Streptococcus pyogenes and Staphylococcus aureus. The petroleum ether extract had a significant effect on Streptococcus pyogenes but Weak effects on both Staphylococcus aureus and Escherichia coli. None of the tested extracts had any effects on Pseudomonas aeruginosa. Conclusion: It is concluded that organic extracts of wheat had antibacterial activity against some of the gram positive and gram negative bacteria.